2006
DOI: 10.1029/2005jd006591
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol constituents and their spatial distribution in the free troposphere of coastal Antarctic regions

Abstract: [1] Direct aerosol sampling of Antarctic aerosols was carried out in the free troposphere over Syowa (39.58°E, 69.00°S) and Mizuho (44.19°E, 70.41°S) stations in April and December 2000 for better understanding of aerosol constituents and their vertical distribution in the Antarctic troposphere. Individual aerosol particles were analyzed/ observed by means of a transmission electron microscope and a scanning electron microscope equipped with an energy dispersive X-ray spectrometer. Aerosol particles containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…Previous aerosol volatility measurements in the AFT deduced that sulfate is the primary component of nanoparticle populations and speculated that biologically produced DMS is the primary precursor (e.g. Iwasaka et al, 1985;Hara et al, 2006). However, composition measurements have not been conclusive.…”
Section: Discussionmentioning
confidence: 88%
“…Previous aerosol volatility measurements in the AFT deduced that sulfate is the primary component of nanoparticle populations and speculated that biologically produced DMS is the primary precursor (e.g. Iwasaka et al, 1985;Hara et al, 2006). However, composition measurements have not been conclusive.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, the derivation of J hom allows for estimation of ice particle production rates from derived homogeneous nucleation according to P ice hom = J hom ·V particle , where V particle is the amount of total liquid volume of aerosol per cm 3 of air. We assume sea salt concentrations, estimated here from field observations of aerosol particle concentrations in the free troposphere as 10 cm −3 (Cziczo et al, 2004;Ikegami et al, , 2004Brock et al, 2011;Hara et al, 2006), with mean dry diameter of 200 nm and a wet diameter of 480 nm at 90 % RH (Zhang et al, 2005;Lewis and Schwartz, 2006), and applying J hom = 10 6 cm −3 s −1 at a temperature of 215 K (Fig. 3), P ice hom could reach 0.035 ice particles L −1 (air) min −1 .…”
Section: Homogeneous Ice Nucleationmentioning
confidence: 99%
“…These previous works indicated (1) aerosol enhancement in free troposphere immediately after cyclone passing (Yamanouchi et al, 1999), (2) appearance of a CN-enhanced layer in lower free troposphere , and (3) transport of sea-salt particles and mineral particles from mid-latitudes through the free troposphere (Yamazaki et al, 1989;Hara et al, 2006). Vertical and seasonal distributions of the aerosol number concentration and constituents in the upper atmosphere, however, are poorly known for Antarctic regions because aerosol measurements in the free troposphere over Antarctica are limited.…”
Section: Introductionmentioning
confidence: 99%
“…They have also been made at inland stations: Dome-F (77 • 19 S 39 • 42 E) , Kohnen (75 • 00 S 00 • 04 E) (Weller et al, 2007), Concordia (75 • S, 123 • E) (Jourdain et al, 2008), and at the South Pole (Amundsen Scott) (90 • S) (Bodhaine, 1995). Some investigations have pointed out the likelihood of aerosol transport through the free troposphere (e.g., Hara et al, 2006) and new particle formation in the free troposphere (Ito et al, 1993;Koponen et al, 2002). Recent works suggested that black carbon, derived mostly from biomass burning, was transported to Antarctic coasts (Fiebig et al, 2009;Hara et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation